Effect of Current Ratio (Cr), Quick Ratio (Qr), Debt To Asset Ratio (Dar) and Debt To Equity Ratio (Der) on Return On Assets (Roa) - Widya Novita Sari; Eri Novari; Yuda Septia Fitri; Ade Iskadar Nasution (Fakultas Ekonomi dan Bisnis Islam, 2022)
This research is motivated by differences in the results of previous studies regarding the Effect of Current Ratio (CR), Quick Ratio (QR), Debt To Asset Ratio (DAR), and Debt To Equity Ratio (DER) on Return On Assets (ROA) in Companies Pharmaceutical Sub-Sector Listed on the Indonesia Stock Exchange for the 2015-2019 Period. This study aims to determine the effect of the Current Ratio (CR), Quick Ratio (QR), Debt To Asset Ratio (DAR), and Debt To Equity Ratio (DER) on Return On Assets (ROA). This study uses several data analyzes, namely descriptive analysis, model selection test, data selection method test (Chow test, Hausman test, and Langrange multiplier test), panel data regression analysis test, hypothesis testing (partial test and simultaneous test), and coefficients. determination by using the Eviews version 10 program. Based on the results of this study, it shows that the measurement results on the Current Ratio (X1) have no significant effect on Return On Assets (Y), Quick Ratio (X2) have no significant effect on Return On Assets (Y), Debt to Assets Ratio (X3) has an effect on Return On Asset (Y), and finally Debt to Equity Ratio (X4) has an effect on Return On Asset (Y).